Numerical Investigation of the Effect Infill from Different Unit cells Structure on Mechanical Behaviour - Imam Akbar; Martin Luther King; Zulkarnain Fatoni; Togar PO Sianipar; Sukarmansyah; Akbar Teguh Prakoso (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
This study aims to identify the effect of infill on mechanical behaviour, especially the yield stress and modulus young of polylactide materials with different unit cell structures such as gyroid, diamond, square, and re-entrant but same porosity with value of 60%. Using Computational aided design (CAD) software and analyzed using the finite element method. The results show that the square structure has the highest strength in terms of mechanical behaviour such as yield stress with a value of 27 MPa, while the gyroid is 25.5 MPa, diamond is 25.3 MPa, re-entrant is 23.3 MPa and young modulus square is 2233MPa gyroid is 2199 MPa, diamond is 2195 MPa re- entrant 2182 MPa. In this study, it was also found that the thickness struth of the unit cell and modulus young had a very strong linear correlation with R2 = 0.96 which explains that the higher the thickness value, the higher the modulus young value. The results of this study also show that although lattice structures, especially square ones, have the highest value, TPMS structures, such as gyroids and diamonds, have more stable performance because these structures have an even stress distribution, thereby reducing the risk of failure of the structure. besides that, the researchers concluded that this TPMS can be used as a solution to improve structural performance.